Demographic variation in fit note receipt and long-term conditions in south London. (24th March 2020) - Dorrington, Sarah; Carr, Ewan; Stevelink, Sharon A M; Dregan, Alexandru; Whitney, David; Durbaba, Stevo; Ashworth, Mark; Mykletun, Arnstein; Broadbent, Matthew; Madan, Ira; Hatch, Stephani; Hotopf, Matthew
Abstract : Objectives: Introduced in the UK in 2010, the fit note was designed to address the problem of long-term sickness absence. We explored (1) associations between demographic variables and fit note receipt, 'maybe fit' use and long-term conditions, (2) whether individuals with long-term conditions receive more fit notes and are more likely to have the 'maybe fit' option selected and (3) whether long-term conditions explained associations between demographic variables and fit note receipt. Methods: Data were extracted from Lambeth DataNet, a database containing electronic medical records of all 45 general practitioner (GP) practices within the borough of Lambeth. Individual-level anonymised data on GP consultations, prescriptions, Quality and Outcomes Framework diagnostic data and demographic information were analysed using survival analysis. Results: In a sample of 326 415 people, 41 502 (12.7%) received a fit note. We found substantial differences in fit note receipt by gender, age, ethnicity and area-level deprivation. Chronic pain (HR 3.7 (95% CI 3.3 to 4.0)) and depression (HR 3.4 (95% CI 3.3 to 3.6)) had the highest rates for first fit note receipt. 'Maybe fit' recommendations were used least often in patients with epilepsy and serious mental illness. The presence of long-term conditions did not explain associations between demographic variables and fit note use. Conclusions: For the first time, we show the relationships between fit note use and long-term conditions using individual-level primary care data from south London. Further research is required in order to evaluate this relatively new policy and to understand the needs of the population it was designed to support.